A Comparative Study on Nitrate Contents in Vegetables between Northern Part of China and the Watershed of Lake Tega in Japan. Issue 1 (March 2021) - Liu, Huan; Huang, Guangwei
Abstract: Humankind is continuously exposed to nitrate through water and food. Excessive intake of nitrate could lead to health problems. Among the food products consumed by human beings, both fresh and processed vegetables are the major source of dietary nitrate intake. In this study, investigations on nitrate contents in vegetables are conducted in the northern part of China and the watershed of Lake Tega in Japan. Four groups of vegetables, leafy, brassica, root and tuber, and fruiting, were sampled for testing. The study focuses on the differences of the nitrate distributions in various crops. As a developed country, Japan has a much stricter regulation on the utilization of nitrogen in fertilizers, with a recommended yield goal N rate of 250 kg/ha/year. Whereas in China, the recommended N rate is 450 kg/ha/year. Meanwhile, the watershed of Lake Tega in Japan has an average annual precipitation of 1348 mm, which is much higher than the Northern part of China. High concentration of nitrate was found in vegetables grown in both Northern China and the watershed of Lake Tega, although the social and environmental conditions are drastically different in these two regions.